2021
DOI: 10.1186/s12893-021-01099-1
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral urothelial carcinoma with squamous cell carcinoma and sarcomatoid carcinoma differentiation: a case report

Abstract: Background Upper urinary tract urothelial carcinoma (UTUC) with multiple pathological types is extremely rare in the clinic, but the recurrence rate and mortality these patients are high. At present, there is no standard treatment for such cases. Case presentation We reported a case of ureteral urothelial carcinoma with squamous cell carcinoma and sarcomatoid carcinoma differentiation and rapid ileal metastasis and reviewed the literature related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…However, sarcomatoid UC is resistant to conventional chemotherapy, and a standard treatment protocol for sarcomatoid UC of the upper urinary tract has not yet been established because of the limited number of cases. To the best of our knowledge, only one case of sarcomatoid UC of the upper urinary tract treated with immunotherapy has been reported to date, and no effectiveness has been confirmed [34]. The patient in our case is the first reported case of sarcomatoid UC of the renal pelvis partially responded to immunotherapy, supporting the prospects of immunotherapy as a promising treatment for this disease.…”
Section: Discussionmentioning
confidence: 55%
“…However, sarcomatoid UC is resistant to conventional chemotherapy, and a standard treatment protocol for sarcomatoid UC of the upper urinary tract has not yet been established because of the limited number of cases. To the best of our knowledge, only one case of sarcomatoid UC of the upper urinary tract treated with immunotherapy has been reported to date, and no effectiveness has been confirmed [34]. The patient in our case is the first reported case of sarcomatoid UC of the renal pelvis partially responded to immunotherapy, supporting the prospects of immunotherapy as a promising treatment for this disease.…”
Section: Discussionmentioning
confidence: 55%
“…According to certain research, patients with higher pT stages may be more likely to benefit from this and get better results from lymph node dissection when using a conventional anatomical template [8]. Ren et al [9] stated that neoadjuvant chemotherapy (NAC) before RNU was shown to produce absolute increases in overall survival by 11%, tumor-specific survival by 18%, and progression-free survival by 13%. This was similarly observed in patients treated with cisplatin-based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, its concurrent association with chondrosarcoma is infrequent. Except for a single case report of high-grade urothelial carcinoma of the right ureter with squamous cell carcinoma and sarcomatoid carcinoma differentiation, no literature is available where both variants exist simultaneously in a case of sarcomatoid urothelial carcinoma [ 8 ].…”
Section: Discussionmentioning
confidence: 99%